MAPPING THE POTENTIALS OF MANEKUNG AS IN AJAR PIKUKUH SUNDA FOR IDEATION PHASE IN CREATION PROCESS BY ETHNOGRAPHIC APPROACH TO BUMI DEGA SUNDA ACADEMY BANDUNG - Sisdianto, Panji
Theoretical Knowledge of Design which is consists of sensory perception, a process of emotion and thought, also the mapping for the creative process that departs from within human as a creator with its intangible nature, makes it difficult to measure, thus making it less desirable. As for a number of theories based on previous research in this scope, still leaving the phenomenon of the creative process as a research landscape that is still broad to explore. Meanwhile a meditation activities were identified by Prof. Primadi Tabrani as part of creative process, which specially placed as the highest stage for both incubation for forming ideas and it’s implementation. Sadly The Prof. did not finished his research until he passed away, without any explanation for what kind of meditation, how, and what potential aspects of it can support the creative process. Overmore there still not much other studies and literatures about meditation in the context of creative process, except more we can find meditation discuss relate to psychology and medical science. In the category of facts, meditation itself is classified as mentifact, interpreted as an intangible cultural relics related to values, ideas, mindset, mental and soul, which is presumed connected to the creativities but still lack of exploration as mentioned. Therefore it is necessary to conduct research on meditation practitioners who also does a creative process. Bandung itself has its own uniqueness by a community established named Bumi Dega Sunda Academy, which has a wisdom teaching call Ajar Pikukuh Sunda or The Way of Life Teaching of Sunda that complemented with such an unknown meditation named Manekung. A numbers of potential informants from various backgrounds were gathered inplace, has a high values to explore the richness understanding of Manekung from many personal phenomenon and point of views (aposteriory). This research is an attempt to answer a number of questions regarding the understanding and procedures of Manekung, and to collect a number of potential aspects of how it works, which are related to the creative 5 process, so that the mapping between this kind of meditation and the creative process becomes clearer. This research conduct in an interdisciplinary approach using the EthnographyCultural Studies method, which is divided into three stages. Social research is held as the first stage, to explore knowledge about the community and its teachings by consist an endure fieldworks, deep interviews, participantobservatory, and documentation collecting. The second stage is textual work, which consists of transforming the collected data to textual matters, based on an inductive principle, which means a broad and detailed description to become a general comprehension with all the authentic findings, but having an oriented understanding. The aim is to build an ideological knowledge base based on Ajar Pikukuh Sunda, and practical knowledge of Manekung. Start from this point, the research entering the third stage. Focused to seek the relation between Manekung as a form of meditation with the creative process which has been theoretically formulated by Tabrani. The conclusion about Manekung is formulated based on ideological, definitive, and practical meanings, which are simplified and represented by keywords: destructiveness, silence, quietness, emptiness, voidness. Manekung is a method for accessing the Universe of Emptiness (Suwung), with the impact of experiencing inner calm. This calmness is a conducive womb for ideas to emerges, then followed up by another stage of work in a creative process. Ethnography-Cultural Studies in this research is a maneuver to gain an output which is enriched the science of design, in general, as on the Theoretical Knowledge category, and specifically, be a complements Tabrani's theory of the creative process. This qualitative study is classified as a soft-science, needs to be followed by quantitative research even within the hard-science based in order to build an inline and complete design knowledge.